Case Report: Filling Defect in Posterior Semicircular Canal on MRI With Balanced Steady-State Gradient-Echo Sequences After Labyrinthine Ischemia in the Common Cochlear Artery Territory as an Early Sign of Fibrosis - Castellucci, Andrea; Pepponi, Emanuela; Bertellini, Annalisa; Senesi, Caterina; Bettini, Margherita; Botti, Cecilia; Martellucci, Salvatore; Malara, Pasquale; Delmonte, Silvia; Crocetta, Francesco Maria; Fornaciari, Martina; Lusetti, Francesca; et al. (Frontiers in Neurology, 2021)
We describe a rare case of posterior semicircular canal (PSC) fibrosis following acute labyrinthine ischemia in the territory supplied by the common cochlear artery (CCA) and review the relevant literature. A 71-year-old man with multiple vascular risk factors presented 12 days after the onset of acute vertigo and profound left-sided hearing loss. Right-beating spontaneous nystagmus with downbeat components elicited by mastoid vibrations and head shakings were detected. The video head impulse test (vHIT) revealed an isolated hypofunction of the left PSC, whereas vestibular evoked myogenic potentials (VEMPs) showed ipsilateral saccular loss. The clinical presentation and instrumental picture were consistent with acute ischemia in the territory supplied by left CCA. Compared to previous imaging, a new MRI of the brain with 3D-FIESTA sequences highlighted a filling defect in the left PSC, consistent with fibrosis. Hearing function exhibited mild improvement after steroid therapy and hyperbaric oxygen sessions, whereas vHIT abnormalities persisted over time. To the best of our knowledge, this is the only case in the literature reporting a filling defect on MRI, consistent with semicircular canal fibrosis following acute labyrinthine ischemia. Moreover, PSC fibrosis was related with poor functional outcome. We therefore suggest using balanced steady-state gradient-echo sequences a few weeks following an acute lesion of inner ear sensors to detect signal loss within membranous labyrinth consistent with post-ischemic fibrosis. Besides addressing the underlying etiology, signal loss might also offer clues on the functional behavior of the involved sensor over time. In cases of acute loss of inner ear function, a careful bedside examination supplemented by instrumental assessments, including vHIT and VEMPs, of vestibular receptors and afferents may be completed by MRI with balanced steady-state gradient-echo sequences at a later time to confirm diagnosis and address both etiology and functional outcome.